The Impact of Restrictions on Labor Rights on the Administrative and Legal Status of Citizens under the Legal Regime of Martial Law: Topical Issues - Korentsov, Oleksandr (Problems of legality, 2026)
Abstract The topic of this research is particularly relevant in view of the limited number of comprehensive studies devoted to ensuring the rights of citizens, especially labor rights, under the legal regime of martial law. The purpose of the article is to analyze the provisions of the Law of Ukraine “On the Legal Regime of Martial Law,” the Law of Ukraine “On the Organization of Labor Relations under Martial Law,” and other regulatory legal acts of the state in terms of their impact on the administrative and legal status of citizens during the period of martial law. In the course of the research, both general scientific and special methods of scientific cognition were employed, including the axiomatic method, the dialectical method, the method of system analysis, the dogmatic method, and the formal-logical method. The study examines the application of such a measure of the martial law regime as compulsory labor service. A systematic analysis of the provisions of the Law of Ukraine “On the Organization of Labor Relations under Martial Law” was carried out, in particular regarding the issue of restrictions on the labor rights of citizens arising from the application of this Law and their compliance with the provisions of the Constitution of Ukraine as well as international legal acts ratified by Ukraine that establish fundamental human and civil rights. The study also analyzes the conditions and factors under which citizens’ labor rights may be restricted. It is concluded that the implementation of the provisions of the Law “On the Organization of Labor Relations under Martial Law,” as well as the measures introduced under the martial law regime, significantly restricts the labor rights of citizens and disrupts the balance of interests between employees and employers in favor of employers. It is further argued that the provisions of this law should be applied only with the consent of the employee. The study concludes that the freedom of will of an employee must not be violated even under the conditions of martial law. Consequently, the Law of Ukraine “On the Organization of Labor Relations under Martial Law” requires substantial amendments. In particular, it is proposed to remove from the text of the law those provisions that allow employers to undertake certain actions without the employee’s consent or that enable the coercive enforcement of employers’ orders or may compel an employee to resign.